Soil Parameters Affecting the Antioxidant Activity of Hypoxis hemerocallidea Corm Extracts in Different Areas of South Africa - Mkolo, N.M.; Olaokun, O.O.; Olowoyo, J.O.; Eloff, J.N.; Naidoo, V. (Asian Journal of Chemistry, 2020)
Hypoxis hemerocallidea is wild harvested and widely used due inter alia to its strong antioxidant activity. Antioxidant activity is linked to plant stressors like soil heavy metals concentrations and pH. If high antioxidant activity is caused by heavy metals stressing the plant, the plant may not be completely safe. Soils and H. hemerocallidea corms were collected from five different geographical regions of South Africa. The highest corm and soil heavy metals concentration were Fe, Mn and Cr, with Fe having the highest, particularly for corms collected from Ga-rankuwa (83.7 ± 0.03 μg/g). The soil and corm samples from Ga-rankuwa with high levels of metals (Fe, Cr, Ni, Pb) had greater antioxidant activity (EC50 of 1.68 ± 0.49 μg/mL). Despite corms showing ability to bio-accumulate heavy metals, the antioxidant activity could not be linked to environmental conditions. The results highlight potential danger of using naturally harvested bulbs growing in unidentified soils.